ERRATUM: Simulation for Neutron Transport in PWR Reactor Moderator and Evaluation for Proper Thickness of Light Water Reflector - -, - (Communications in Physics, 2015)
ERRATUM: Simulation for Neutron Transport in PWR Reactor Moderator and Evaluation for Proper Thickness of Light Water Reflector [Nguyen Tuan Khai and Phan Quoc Vuong, Comm. Phys. 25(1) (2015) 91--96]